2021
DOI: 10.3324/haematol.2020.263392
|View full text |Cite
|
Sign up to set email alerts
|

A phase I/II study of the combination of quizartinib with azacitidine or low-dose cytarabine for the treatment of patients with acute myeloid leukemia and myelodysplastic syndrome

Abstract: FMS-like tyrosine kinase 3-internal tandem duplication (FLT3-ITD) mutation in acute myeloid leukemia (AML) is associated with poor prognosis. We hypothesized that quizartinib, a selective and potent FLT3 inhibitor, with azacitidine (AZA) or low-dose cytarabine (LDAC) might improve the outcomes in patients with FLT3-ITD-mutated AML. In this open-label phase I/II trial, patients of any age receiving first-salvage treatment for FLT3-ITD AML or age >60 years with untreated myelodysplastic syndrome or AML were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 35 publications
0
27
0
1
Order By: Relevance
“…Pre-clinical studies in FLT3 mut cell lines, primary samples, and xenografts have shown a synergy between FLT3i and VEN through downregulation of MCL-1 and BCL-XL [ 81 , 82 , 83 ]. Prior clinical studies have demonstrated the safety and efficacy of the combination of SORA, quizartinib, or GILT with HMA, with an ORR of 65–80% and median OS 8.5–20 months [ 84 , 85 , 86 , 87 ].…”
Section: Clinical Studies Of Ven In Amlmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-clinical studies in FLT3 mut cell lines, primary samples, and xenografts have shown a synergy between FLT3i and VEN through downregulation of MCL-1 and BCL-XL [ 81 , 82 , 83 ]. Prior clinical studies have demonstrated the safety and efficacy of the combination of SORA, quizartinib, or GILT with HMA, with an ORR of 65–80% and median OS 8.5–20 months [ 84 , 85 , 86 , 87 ].…”
Section: Clinical Studies Of Ven In Amlmentioning
confidence: 99%
“…Consistently, clinical studies identified lower response and survival rates in patients with AML and TP53 alterations [ 44 , 46 , 48 ]. A retrospective analysis of 121 patients treated with DEC10-VEN frontline therapy in a phase II trial was performed to specifically assess the role of TP53 mutations [ 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ...…”
Section: Molecular Factors Driving Resistancementioning
confidence: 99%
“…Moreover, the median overall survival was enhanced in the combination therapy cohort. These results give evidence for the effectiveness of quizartinib as a combination therapy, specifically with azacytidine, in patients with FLT3-ITD-mutated AML [ 49 ].…”
Section: Reviewmentioning
confidence: 98%
“…The corresponding inhibitors (ivosidenib and enasidenib) have shown encouraging results in AML patients and are currently tested in higher-risk MDS setting [155][156][157][158]. Other target therapies for higher-risk MDS, adopted from AML treatment, include the FLT-3 inhibitors (midostaurin, gilteritinib, and quizartinib), which are investigated in phase 2 clinical trials [159][160][161]. Cellular-based immune-therapies are of increasing interest.…”
Section: Higher-risk Mdsmentioning
confidence: 99%